Meningkatkan Hasil Belajar Siswa dengan Metode Demonstrasi pada Permainan Bola Basket di Sekolah Dasar - Hafridarli Hafridarli (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study is to improve student learning outcomes on basketball games with demonstration methods for students of class 5 SDN 22 Koto Baru. Research methods that researchers use for classroom action research is action research conducted in the classroom to improve student learning outcomes. This study was conducted in 2 cycles. Each cycle consists of planning, implementation, observation, and reflection. This research was conducted at SDN 22 Koto Baru. This research was conducted in August with the november 2017 in 5 C SDN 22 Koto Baru class, the result of the research shows that learning by demonstration method can not only improve the students learning outcomes on the knowledge aspect but also can improve the students skills because the students in the learning are asked directly demonstrating the movements in basketball games. Thus, it is suggested that teachers are expected to use demonstration methods in learning and students should listen to any information submitted by the teacher, so that the learning will run smoothly. Keywords: learning outcomes, demonstration methods, basketball games